2019
DOI: 10.3332/ecancer.2019.980
|View full text |Cite
|
Sign up to set email alerts
|

Advances in pain management for older patients with cancer

Abstract: The population of older patients is growing with a rising prevalence of cancer diagnoses and cancer-related pain syndromes. Older patients are also vulnerable to misleading pain evaluations and under treatment with opioids. Barriers to the effective and safe management of analgesics include pain assessments and the complex management of the best analgesic choice and dose-titration while achieving the fewest side effects. In this review, we will provide an overview of the challenges present in assessment and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…Conversely, a 2019 network meta-analysis of analgesic drugs for chronic cancer pain concluded that the top-ranking drug classes for global efficacy were non-opioid analgesics, including paracetamol, as well as NSAIDs and opioids [ 126 ]. It is considered the first-choice drug for mild-to-moderate pain in older patients with cancer naïve to opioids [ 127 ].…”
Section: Clinical Guidelinesmentioning
confidence: 99%
“…Conversely, a 2019 network meta-analysis of analgesic drugs for chronic cancer pain concluded that the top-ranking drug classes for global efficacy were non-opioid analgesics, including paracetamol, as well as NSAIDs and opioids [ 126 ]. It is considered the first-choice drug for mild-to-moderate pain in older patients with cancer naïve to opioids [ 127 ].…”
Section: Clinical Guidelinesmentioning
confidence: 99%
“…In the emergency room, assessment should start by ruling out a life-threatening medical emergency revealed by pain, cancer, or non-cancer related, followed by a quick relief of the uncontrolled cancer pain. Assessment of pain includes symptom and patient characterization, classification of etiology of pain, and identification of cancer syndrome 48,49 .…”
Section: Risk Factors and Assessment In The Ed Settingmentioning
confidence: 99%
“…Several screening tools had been implemented and until now none have been superior to the others. The Checklist of Non-verbal Pain Indicators (CNPIs) and the Pain Assessment in Advanced Dementia Scale (PAINNAD) are some screening tools that can be used in these populations 49,50 . Patient characterization must include comorbidities, on-going and past treatments, and the impact of pain on functionality, malnutrition, and psychological state.…”
Section: Risk Factors and Assessment In The Ed Settingmentioning
confidence: 99%
“…The assessment of pain in elderly patients is particularly difficult because, despite the more frequent experience of pain, they report it less frequently than younger patients [27]. This is because they show greater tolerance to pain, recognizing that it is an inherent part of the ageing process, and deny its existence.…”
Section: Assessment Of Pain Intensitymentioning
confidence: 99%